PENERAPAN EKSAMINASI TERHADAP KASUS HUKUM DI LINGKUNGAN KEJAKSAAN - TITIN APRIANI (GANEC SWARA, 2023)
As an oversight, examination is not the only supervision in the Prosecutor's Office. There are still many other controls that are carried out both internally and externally. It's just whether the supervision is effective or not. The purpose of this study is to find out how the form of examination in the prosecutor's office is and how it is applied to cases that are rampant, then the research method used is the type of normative research and the approach method is the approach to legislation, conceptual approach and supported by historical and historical approaches. case. The results of the discussion that there are two types of examinations in the prosecutor's office, namely general examinations and special examinations, the conclusion of the discussion is that there are still many cases that have not been noticed so that they need to be examined.